A sodium-sulfur solid-state battery positive electrode active material and its preparation method and application
By adding carbon nanodispersive additives and forming active sulfides to the positive electrode active material of sodium-sulfur solid state battery, the problem of performance degradation caused by the inability to fully exert capacity and volume changes is solved, and the effect of improving the battery charge and discharge performance and cycle stability is achieved.
Patent Information
- Application Number
- CN202411606024.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The positive electrode active material of sodium-sulfur solid state batteries cannot fully exert its capacity, and the volume changes greatly during the charging and discharging process, resulting in capacity loss and degradation of battery performance.
Carbon nanodispersion additives are added during the preparation of the positive electrode active material of sodium-sulfur solid battery, and active sulfides are formed through the reaction of sulfur and sodium metal, and combined with the carbon nanodispersion additives to form a conductive network to improve electron transmission efficiency and improve the reaction contact area through mechanical mixing and processing.
It improves the charge and discharge performance and rate performance of the battery, reduces charge accumulation and polarization, enhances the overall stability and cycle stability of the material, and extends the cycle life of the battery.
Smart Images

Figure CN119160860B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sodium ion solid-state battery, and in particular to a sodium-sulfur solid-state battery positive electrode active material, a preparation method and an application thereof. Background Art
[0002] Sodium-sulfur solid-state battery is an advanced electrochemical energy storage device that uses sodium ions as charge carriers and solid electrolytes for ion conduction. During the charging process, sodium ions migrate from the positive electrode to the negative electrode through the solid electrolyte and are stored; during discharge, sodium ions return from the negative electrode to the positive electrode, forming a current through the external circuit, thereby achieving energy storage and release.
[0003] The positive electrode of traditional sodium solid-state batteries can be layered transition metal oxides, polyanionic compounds, O3 and P2 oxide materials, phosphates, fluorophosphates, silicates, thorium blue compounds or organic positive electrode materials, however, the theoretical electrochemical capacity of these active materials is low.
[0004] The sodium-sulfur solid-state battery is based on the direct conversion reaction of sulfur: S+2Na=Na2S. Therefore, the sodium-sulfur solid-state battery uses sulfide active materials as the positive electrode material. Compared with traditional active materials, sulfide active materials have a higher theoretical electrochemical capacity (1675mAh / g in terms of elemental sulfur, 860mAh / g and 480mAh / g in terms of sodium sulfide and disulfide, respectively). At the same time, unlike the liquid electrolyte system, the process of polysulfide formation during the reaction of the sodium-sulfur solid-state battery is more controllable, thereby improving the electrochemical performance and improving safety.
[0005] However, despite the high specific energy characteristics of sulfur and sulfide particles, their low electrical conductivity makes it difficult to fully utilize the theoretical capacity of sulfur-based cathodes. Attempts have been made to use only active materials as working electrodes to make solid-state Na / S batteries, which experience large changes in the volume of active material particles during the charge / discharge process, inevitably leading to capacity loss and battery performance degradation.
[0006] The patent with application number CN201710526097.3 discloses a sodium-sulfur battery positive electrode material and a preparation method thereof. The invention relates to a sodium-sulfur positive electrode material and a preparation method thereof, which is composited with a metal organic framework material and sublimated sulfur, wherein the mixing mass ratio of the metal organic framework material and the sublimated sulfur is 1:1-1:4, and the sulfur loading is 60-75%, and comprises the following steps: a) heat-treating the metal organic framework material to obtain a graphitized porous material; b) mixing the graphitized porous material obtained in step a) with sublimated sulfur, grinding, and heat-treating the material to allow sulfur to penetrate into the porous material to obtain the sodium-sulfur battery positive electrode material. Compared with the prior art, the invention has the advantages that the mesopores load most of the active substances, which helps to inhibit the diffusion of polysulfide ions and effectively limit the dissolution of polysulfide during the cycle. At the same time, the specific surface area is large, which can provide a larger reaction interface and also plays a certain role in adsorbing sulfur and polysulfide. Summary of the invention
[0007] The present invention aims to overcome the defects that the positive electrode active material of the sodium-sulfur solid-state battery in the prior art cannot fully exert its capacity and its volume will change significantly during the charging and discharging process, resulting in capacity loss and battery performance degradation. Therefore, a sodium-sulfur solid-state battery positive electrode active material and its preparation method and application are provided.
[0008] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:
[0009] In a first aspect, the present invention first provides a method for preparing a positive electrode active material for a sodium-sulfur solid-state battery, comprising the following steps:
[0010] (S.1) adding sodium salt and carbon nanodispersing additive into a non-protonic solvent and performing mechanical mixing to form a suspension;
[0011] (S.2) adding finely dispersed sulfur to the resulting suspension at once and adding metallic sodium chips stepwise under mechanical mixing conditions until the metallic sodium is consumed;
[0012] (S.3) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is ground to obtain the positive electrode active material of the sodium ion solid-state battery.
[0013] The sodium-sulfur solid-state battery positive electrode active material in the present application mainly includes the following three technical points in the preparation process: (1) a certain amount of carbon nano-dispersed additives are added to the sodium-sulfur solid-state battery positive electrode active material reaction system; (2) the present application forms active sulfide through the reaction between sulfur and metallic sodium, and combines it with the carbon nano-dispersed additive; (3) mechanical mixing processing is adopted in the present application.
[0014] Among them, for the first technical point: the present application adds a certain amount of carbon nano-dispersed additives to the reaction system. Since carbon nano-materials have excellent electrical conductivity, carbon nano-additives can form a conductive network in the positive electrode active material, improve the transmission efficiency of electrons in the material, thereby reducing the internal resistance of the battery and improving the battery's charge and discharge performance and rate performance. When the battery is charged and discharged, electrons can be quickly transmitted to the surface of the active sulfide through the carbon nano-network to participate in the redox reaction. This efficient electron conduction can reduce charge accumulation and polarization phenomena, and improve the battery's charge and discharge efficiency and rate performance. At the same time, carbon nano-additives can also balance the charge distribution in the active sulfide, reduce local charge concentration, and thus reduce the probability of material degradation and side reactions.
[0015] In addition, carbon nanomaterials have high strength and toughness. In the positive electrode active material, carbon nano-dispersed additives can form a three-dimensional network structure to provide physical support for the active sulfide. Therefore, when the battery undergoes volume changes during charging and discharging, the carbon nano-network can effectively resist external stress and prevent the nanostructure of the active sulfide from collapsing and breaking. For example, during repeated charge and discharge cycles, the active sulfide may expand and contract in volume due to the insertion and extraction of sodium ions. The presence of carbon nano-additives can reduce the damage to the material structure caused by this volume change, thereby improving the cycle stability of the battery.
[0016] In addition, active sulfide is prone to aggregation of nanoparticles during preparation and use, and the present application can prevent the aggregation of active sulfide nanoparticles by adding carbon nano dispersion additives during the preparation of positive electrode active materials through physical barrier effect, and can adsorb and fix active sulfide nanoparticles through the high specific surface area and surface activity of carbon nanomaterials to keep them dispersed. This can increase the contact area between the active material and the electrolyte, improve the ion transmission efficiency, and thus improve the performance of the battery.
[0017] There may be chemical bonding between carbon nanomaterials and active sulfides. For example, the functional groups on the surface of carbon nanotubes can form covalent bonds or coordination bonds with the sulfur atoms in the active sulfides. This chemical bonding can enhance the binding force between carbon nanomaterials and active sulfides and improve the overall stability of the material. At the same time, chemical bonding can also promote the transmission of electrons in the material, improving the conductivity and reaction kinetics of the battery.
[0018] Regarding the second technical point: Sulfur as a positive electrode active material has a high theoretical specific capacity. In this application, the positive electrode active material formed by reacting finely dispersed sulfur with sodium salt and metallic sodium can give full play to the high specific capacity advantage of sulfur and improve the energy storage capacity of the battery. Among them, metallic sodium (Na) is an active metal with strong reducing properties. Sulfur (S) can react chemically with metallic sodium under certain conditions to generate sodium sulfide (Na2S) and sodium polysulfide (Na2S x , x>1). The reaction process can be divided into the following stages:
[0019] Initial reaction: When metallic sodium turnings come into contact with finely dispersed sulfur, the first reaction that occurs is the direct combination of sodium and sulfur to form sodium sulfide:
[0020] 2Na + S → Na2S;
[0021] Further reaction: As the reaction proceeds, the generated sodium sulfide will continue to react with sulfur to form sodium polysulfide:
[0022] Na2S + (x - 1)S → Na2S x ;
[0023] The value of x depends on the reaction conditions and the sulfur content.
[0024] The formation of sodium polysulfide is a dynamic process, and the composition of sodium polysulfide will continue to change as the reaction proceeds. During the reaction, sulfur particles and metallic sodium are solid substances that are difficult to dissolve in aprotic solvents, so it is difficult for both to enter the interior of the carbon nano-dispersed additive. When sulfur particles and metallic sodium react, sodium sulfide and sodium polysulfide that can be dissolved in the solvent can be formed, so they can enter the interior of the carbon nano-dispersed additive, so that the carbon nano-dispersed additive can provide physical structural support and chemical interaction for the positive electrode active material, can effectively stabilize the nanostructure of the active sulfide positive electrode material, and improve the performance and cycle stability of the battery.
[0025] In addition, during the reaction process, the present application also adds a certain amount of sodium salt in the preparation process of the positive electrode active material of the sodium ion solid-state battery. The reason is that during the preparation process, the sodium salt reacts with sulfur and metallic sodium to generate sulfides and polysulfides containing sodium ions, which are the main components of the positive electrode active material. Therefore, by selecting different sodium salts and controlling the amount of sodium salts, the concentration of sodium ions in the positive electrode active material can be adjusted. And the appropriate sodium ion concentration is crucial to the performance of the battery. If the sodium ion concentration is too high, it may cause the material structure to be unstable and affect the cycle life of the battery; if the sodium ion concentration is too low, it may reduce the energy density and power performance of the battery. Therefore, selecting a suitable sodium salt and controlling its amount can optimize the performance of the positive electrode active material.
[0026] In addition, some sodium salts can act as dispersants to promote the dispersion of carbon nano-dispersed additives and sulfur in aprotic solvents. Good dispersibility helps to improve the uniformity and reactivity of the material. For example, some sodium salts can reduce the surface tension of the solution, making it easier for carbon nano-dispersed additives and sulfur to disperse in the solvent to form a stable suspension. This uniform dispersion state is conducive to subsequent reactions and material formation, and improves the performance of positive electrode active materials. Some sodium salts may have certain ionic conductivity and can play a role in conducting sodium ions in positive electrode active materials. Improving the conductivity of the material helps to reduce the internal resistance of the battery and improve the battery's charge and discharge performance and rate performance.
[0027] Regarding the third invention point: As mentioned above, in the reaction process described in the present application, the metallic sodium chips and the finely dispersed sulfur are both solid substances, and the reaction between them is a solid-solid reaction. Generally speaking, the rate of solid-solid reactions is usually slow, so in the present application, mechanical mixing processing and other methods are used to increase the contact area and reaction rate of the reaction.
[0028] Preferably, the mass ratio of the sodium salt, the carbon nano-dispersed additive, the finely dispersed sulfur and the metallic sodium chips is 105:5:(32-64):54.
[0029] Preferably, the sodium salt is sodium perchlorate, sodium bis(fluorosulfonyl)imide or a combination of both.
[0030] Preferably, the mechanical mixing processing method in step (S.1) includes any one of an impact mill, a high shear mixer and a ball mill.
[0031] Preferably, in the step (S.2), the metallic sodium chips are added in 10-15 portions within 1-2 hours.
[0032] The reaction of metallic sodium and sulfur is a strong exothermic reaction. During the reaction, a large amount of heat is released, which increases the temperature of the reaction system. This exothermic reaction needs to be controlled under appropriate conditions to prevent the reaction from being too violent and causing safety problems. Therefore, the present application adjusts the reaction rate by adding metallic sodium chips step by step.
[0033] Preferably, the surface of the carbon nano-dispersed additive is coated with a carbon coating layer, and the carbon coating layer is doped with nitrogen atoms.
[0034] In a preferred embodiment of the present application, the surface of the carbon nano-dispersed additive is also coated with a carbon coating layer doped with nitrogen atoms. The applicant has found that: although carbon itself has good electrical conductivity, the electrical conductivity of the carbon nano-dispersed additive is further enhanced after a layer of carbon coating layer is coated on its surface. In the positive electrode active material of the sodium ion solid-state battery, good electrical conductivity contributes to the rapid transmission of electrons in the material, which can reduce the internal resistance of the battery and improve the charge and discharge efficiency and rate performance of the battery. For example, during high-rate charge and discharge, electrons can reach the surface of the active material more quickly to participate in the reaction, reducing energy loss and polarization. The reason is that the doping of nitrogen atoms can introduce additional electronic defects and active sites in the carbon coating layer. These defects and sites can change the electronic structure of the carbon material and improve its electronic conductivity.
[0035] In addition, the carbon coating layer can be used as a protective layer to prevent the carbon nano-dispersed additive from being affected by the external environment during the preparation and use process and causing structural damage or performance degradation. Therefore, during the charge and discharge process of the battery, the carbon coating layer can buffer the volume change and chemical stress that the positive electrode material will experience, protect the nanostructure of the carbon nano-dispersed additive, and maintain its stability and performance. In addition, the carbon coating layer can keep the nanoparticles in a dispersed state through steric hindrance and electrostatic repulsion, prevent the nanoparticles of the carbon nano-dispersed additive from aggregating, and improve the ion transmission efficiency and reaction rate.
[0036] The nitrogen atoms doped in the carbon coating layer can form stronger chemical bonds or interactions with the positive electrode active material sulfur. This interaction can improve the binding stability between the carbon nano-dispersed additive and sulfur, and prevent the loss and shuttle effect of sulfur during the charge and discharge process. For example, nitrogen atoms can form covalent bonds or coordination bonds with sulfur atoms, enhance the adsorption and fixation of sulfur on the surface of the carbon nano-dispersed additive, and improve the cycle stability and coulomb efficiency of the positive electrode active material. The presence of nitrogen atoms can introduce more ion adsorption sites and transmission channels, and promote the diffusion and migration of sodium ions in the positive electrode material. This helps to improve the charge and discharge performance and cycle life of the battery.
[0037] Preferably, the carbon coating layer is prepared as follows: a carbon nano-dispersed additive is added to a polymer monomer containing nitrogen atoms, and the polymer monomer containing nitrogen atoms is polymerized in situ on the surface of the carbon nano-dispersed additive to obtain a nitrogen atom-containing polymer, and the nitrogen atom-containing polymer is thermally decomposed to obtain the carbon coating layer.
[0038] In a second aspect, the present application also provides a positive electrode active material for a sodium-sulfur solid-state battery, which is prepared by any of the methods described above.
[0039] In a third aspect, the present application also provides a sodium-sulfur solid-state battery, which includes the positive electrode active material for the sodium-sulfur solid-state battery.
[0040] Therefore, the present invention has the following beneficial effects:
[0041] (1) In the process of preparing the positive electrode active material of the sodium-sulfur solid-state battery, the present application adds a certain amount of carbon nano-dispersed additive to the reaction system, which can effectively adsorb the prepared active sulfide, thereby providing physical support for the active sulfide and preventing the nanostructure collapse and breakage caused by the volume change of the active sulfide during the charge and discharge process of the battery;
[0042] (2) The active sulfide in the present application is obtained by in-situ reaction of sodium salt, finely dispersed sulfur and metallic sodium. Its particle size is smaller and does not aggregate, so that the active sulfide has a high specific surface area and surface activity, thereby increasing the contact area between the active material and the electrolyte, improving the ion transfer efficiency, and thus improving the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an electron microscope photograph of the prepared sodium-sulfur solid-state battery positive electrode active material.
[0044] Figure 2 This is a photo of the positive electrode of the prepared sodium-sulfur solid-state battery and its electron microscope photo. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0046] Example 1
[0047] A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery comprises the following steps:
[0048] (S.1) 150 parts of sodium perchlorate and 5 parts of carbon nanotubes were added to 850 parts of tetraethylene glycol dimethyl ether (TEGDME), and mechanical mixing was performed using a high shear mixer at a speed of 1500 rpm for 30 minutes to form a suspension;
[0049] (S.2) 32 parts of finely dispersed sulfur are added to the obtained suspension at one time, and at the same time, 54 parts by mass of metallic sodium chips are added in 15 portions within 2 hours under mechanical mixing conditions until the sodium is consumed;
[0050] (S.3) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is dry-milled and particles smaller than 1 µm are collected at an outlet to obtain the sodium-sulfur solid-state battery positive electrode active material.
[0051] The obtained sodium-sulfur solid-state battery positive electrode active material was observed using an electron microscope, and the results are as follows Figure 1 shown. Figure 1 The upper left part of the middle figure is a model diagram of active sulfide particles protected by carbon nanomaterials; Figure 1 Lower left center: Scanning electron micrograph of active sulfide particles covered by carbon nanomaterials. Figure 1 On the right is a transmission electron micrograph of sulfide particles between carbon nanomaterials.
[0052] Example 2
[0053] A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery comprises the following steps:
[0054] (S.1) 120 parts of sodium perchlorate and 10 parts of carbon nanotubes were added to 850 parts of tetraethylene glycol dimethyl ether (TEGDME), and mechanical mixing was performed using a high shear mixer at a speed of 1000 rpm for 60 minutes to form a suspension;
[0055] (S.2) 40 parts of finely dispersed sulfur are added to the obtained suspension at one time, and at the same time, 40 parts by mass of metallic sodium chips are added in 12 portions within 1 hour under mechanical mixing conditions until the sodium is consumed;
[0056] (S.3) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is dry-milled and particles smaller than 1 µm are collected at an outlet to obtain the sodium-sulfur solid-state battery positive electrode active material.
[0057] Example 3
[0058] A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery comprises the following steps:
[0059] (S.1) 100 parts of sodium perchlorate and 6 parts of graphene powder were added to 850 parts of dimethyl sulfoxide (DMSO), and mechanical mixing was performed using a high shear mixer at a speed of 1000 rpm for 60 minutes to form a suspension;
[0060] (S.2) 64 parts of finely dispersed sulfur are added to the obtained suspension at once, and at the same time, 60 parts by mass of metallic sodium chips are added in 10 portions within 2 hours under mechanical mixing conditions until the sodium is consumed;
[0061] (S.3) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is dry-milled and particles smaller than 1 µm are collected at an outlet to obtain the sodium-sulfur solid-state battery positive electrode active material.
[0062] Example 4
[0063] A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery comprises the following steps:
[0064] (S.1) 120 parts of sodium bis(fluorosulfonyl)imide and 8 parts of graphene powder were added to 850 parts of tetraethylene glycol dimethyl ether (TEGDME), and mechanical mixing was performed using a high shear mixer at a speed of 1500 rpm for 30 minutes to form a suspension;
[0065] (S.2) 50 parts of finely dispersed sulfur are added to the obtained suspension at one time, and at the same time, 50 parts by mass of metallic sodium chips are added in 15 portions within 1 hour under mechanical mixing conditions until the sodium is consumed;
[0066] (S.3) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is dry-milled and particles smaller than 1 µm are collected at an outlet to obtain the sodium-sulfur solid-state battery positive electrode active material.
[0067] Example 5
[0068] A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery comprises the following steps:
[0069] (S.1) Add 5 parts of graphene powder to 100 parts of 0.5 mol / L dopamine hydrochloride solution, adjust the pH of the solution to 8.5, stir and react for 24 hours, and allow dopamine hydrochloride to polymerize in situ on the surface of the graphene powder to obtain polydopamine, then heat the polymer graphene powder coated with polydopamine to 500°C under nitrogen protection for 3 hours to perform thermal decomposition, thereby surface-modifying the graphene powder;
[0070] (S.2) adding 150 parts of sodium perchlorate and 5 parts of surface-modified graphene powder to 850 parts of tetraethylene glycol dimethyl ether (TEGDME), and performing mechanical mixing processing using a high shear mixer at a speed of 1500 rpm for 30 minutes to form a suspension;
[0071] (S.3) 32 parts of finely dispersed sulfur are added to the obtained suspension at one time, and at the same time, 54 parts by mass of metallic sodium chips are added in 15 portions within 2 hours under mechanical mixing conditions until the sodium is consumed;
[0072] (S.4) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is dry-milled and particles smaller than 1 µm are collected at an outlet to obtain the sodium-sulfur solid-state battery positive electrode active material.
[0073] Example 6
[0074] A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery comprises the following steps:
[0075] (S.1) Add 50 parts of carbon nanotubes to 500 parts of a 0.5 mol / L dopamine hydrochloride solution, adjust the pH of the solution to 8.5, stir and react for 24 hours, and allow dopamine hydrochloride to polymerize in situ on the surface of graphene powder to obtain polydopamine, then heat the polymer graphene powder coated with polydopamine to 500°C under nitrogen protection for 3 hours to thermally decompose the surface of the carbon nanotubes;
[0076] (S.2) adding 120 parts of sodium perchlorate and 10 parts of surface-modified carbon nanotubes to 850 parts of tetraethylene glycol dimethyl ether (TEGDME), and performing mechanical mixing processing using a high shear mixer at a speed of 1000 rpm for 60 minutes to form a suspension;
[0077] (S.3) 40 parts of finely dispersed sulfur are added to the obtained suspension at one time, and at the same time, 40 parts by mass of metallic sodium chips are added in 12 portions within 1 hour under mechanical mixing conditions until the sodium is consumed;
[0078] (S.4) The suspension is vacuum spray dried, the solvent is recovered to obtain a dry residue, and the dry residue is dry-milled and particles smaller than 1 µm are collected at an outlet to obtain the sodium-sulfur solid-state battery positive electrode active material.
[0079] Comparative Example 1
[0080] The difference between Comparative Example 1 and Example 1 is that there is no addition of carbon nanotubes in step (S.1).
[0081] Comparative Example 2
[0082] The difference between Comparative Example 2 and Example 1 is that there is no addition of sodium perchlorate in step (S.1).
[0083] Comparative Example 3
[0084] The difference between Comparative Example 3 and Example 1 is that sodium sulfide is directly added in step (S.2) and treated for 2 hours under mechanical mixing processing conditions.
[0085] Performance Test:
[0086] Preparation of sodium-sulfur solid-state battery: 10 parts of sodium-sulfur solid-state battery positive electrode active materials prepared in Examples 1-6 and Comparative Examples 1-3 and 1 part of binder polyvinylidene fluoride and nitrogen methyl pyrrolidone solution are prepared into a slurry with a solid content of 50%, and the slurry is evenly coated on the surface of carbon-coated aluminum foil (i.e., positive electrode current collector) and vacuum dried to prepare the positive electrode of the sodium-sulfur solid-state battery. The photo and electron micrograph of the positive electrode of the sodium-sulfur solid-state battery are shown in FIG. Figure 2 shown.
[0087] The sodium metal foil is then compacted and used as the negative electrode of the battery. At the same time, β-alumina is used as a solid electrolyte. The positive electrode, solid electrolyte and negative electrode of the sodium-sulfur solid-state battery are assembled to obtain a sodium-sulfur solid-state battery.
[0088] Performance test: The specific capacity of the prepared sodium-sulfur solid-state battery was tested in the charge and discharge voltage range of 0.5V-3.0V and the charge and discharge current density of 50 mA / g. The specific test results of the sodium-sulfur solid-state batteries in Examples 1-6 and Comparative Examples 1-3 are shown in Table 1 below.
[0089] Table 1
[0090] project Specific capacity (mAh / g) First effect (%) 100 cycles capacity retention rate (%) Example 1 618.84 76.16 80.3 Example 2 615.84 77.81 79.1 Example 3 635.09 80.32 82.5 Example 4 623.79 78.96 81.9 Example 5 605.16 82.62 88.6 Example 6 619.35 85.82 89.3 Comparative Example 1 219.82 63.62 32.1 Comparative Example 2 308.06 65.69 72. 9 Comparative Example 3 259.35 70.36 58.6
[0091] It can be seen from the data in Table 1 that the sodium-sulfur ion solid-state battery positive electrode active material prepared in this application has a high specific capacity and first efficiency, and it also has good cycle stability (100 cycles of capacity retention rate of more than 80%). This shows that the present invention synergizes the active sulfide formed by the carbon nano-dispersed additive with the in-situ reaction to provide physical support for the active sulfide, thereby preventing the nanostructure collapse and breakage caused by the volume change of the active sulfide during the charge and discharge process of the battery. At the same time, because the particle size of the active sulfide is finer, it has a high specific surface area and surface activity, thereby increasing the contact area between the active substance and the electrolyte, improving the ion transfer efficiency, and thus improving the performance of the battery.
[0092] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but this will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a positive electrode active material for a sodium-sulfur solid-state battery, characterized in that: The following steps are involved: (S.1) adding sodium salt and carbon nanodispersing additive into a non-protonic solvent and performing mechanical mixing to form a suspension; (S.2) adding finely dispersed sulfur to the resulting suspension at once and adding metallic sodium chips stepwise under mechanical mixing conditions until the sodium is consumed; (S.3) drying the suspension by vacuum spray drying, recovering the solvent to obtain a dry residue, and grinding the dry residue to obtain the sodium-sulfur solid-state battery positive electrode active material; The mass ratio of the sodium salt, the carbon nano-dispersed additive, the finely dispersed sulfur and the metallic sodium chips is (100-150): (10-5): (32-64): (40-60); The sodium salt is one or a combination of sodium perchlorate and sodium bis(fluorosulfonyl)imide; The carbon nanometer dispersion additive is one of carbon nanometer tubes and graphene powder or a combination of the two.
2. The method for preparing a positive electrode active material for a sodium-sulfur solid-state battery according to claim 1, characterized in that: The mechanical mixing processing method in the step (S.1) includes any one of an impact mill, a high shear mixer and a ball mill.
3. The method for preparing a positive electrode active material for a sodium-sulfur solid-state battery according to claim 1, characterized in that: In the step (S.2), the metallic sodium chips are added in 10-15 portions within 1-2 hours.
4. The method for preparing a positive electrode active material for a sodium-sulfur solid-state battery according to claim 1, characterized in that: The surface of the carbon nano-dispersed additive is coated with a carbon coating layer, and the carbon coating layer is doped with nitrogen atoms.
5. The method for preparing a positive electrode active material for a sodium-sulfur solid-state battery according to claim 4, characterized in that: The preparation method of the carbon coating layer is as follows: adding a carbon nano-dispersed additive to a polymer monomer containing nitrogen atoms, and polymerizing the polymer monomer containing nitrogen atoms in situ on the surface of the carbon nano-dispersed additive to obtain a nitrogen atom-containing polymer, and thermally decomposing the nitrogen atom-containing polymer to obtain the carbon coating layer.
6. A positive electrode active material for a sodium-sulfur solid-state battery, characterized in that: The invention is prepared by the method according to any one of claims 1 to 5.
7. A sodium-sulfur solid-state battery, characterized in that: Comprising the positive electrode active material for a sodium-sulfur solid-state battery as described in claim 6.
Citation Information
Patent Citations
Sodium-sulfur battery positive electrode material and preparation method therefor
CN107317013A
Graphene-coated carbon nanofiber / sulphur composite material, preparation and application thereof
CN104269538A
Sulfur-carbon composite material and preparation method thereof
CN105047861A